Genetic aspects of criteria of trypanotolerance - Trail, J.C.M.; D'Ieteren, G.D.M.; Feron, A.; Itty, P.; Kakiese, O.; Maehl, J.H.H.; Mulungo, M.; Nagda, S.M.; Paling, R.W.; Pelo, M.; Rarieya, J.M.; Thorpe, W.R. (1988)
In Mushie ranch, 157 N`Dama progeny of four sires, 95 males and 62 females, were used to estimate the habitability levels for aspects of parasitaemia, anemia control, immune response and animal performance. The males were exposed to a high natural trypanosome challenge, and body weight, trypanosome aspects and PCVS were recorded weekly on eleven occasions covering a ten-week period. The females were exposed to a low natural trypanosome challenge and recorded weekly on eight occasions covering a seven-week period. In the high-challenge and low-challenge situations, the habitability estimates for daily liveweight change were 0.20 and 0.68, respectively. But there was no indication of any of the aspects of parasitaemia being heritable. In males under a high challenge, the habitability estimate for PCV level was 0.15.